Sistem Pemilihan Bakal Calon Legislatif oleh Partai Politik dengan Metode Simple Additive Weighting - Alpionita , Ella; Hutahaean, Jeperson; Dewi, Muthia (Universitas Hamzanwadi, 2024)
The Regional Leadership Council of the Grinding Party experienced difficulties during the general election in 2019 where legislative candidates could not meet the party's target of 2 seats. So that in 2024 before the general election a decision support system-based legislative candidate selection system was created so that for future plans the party will use this system so it is necessary to start building the system. The purpose of this research is to be able to determine prospective candidates to become legislative candidates. This type of research is quantitative in criteria data collection techniques can also be through observation, interviews and literature studies, with an application development model using a prototype model. The prototype model with the stages of collecting data and case examples, designing prototypes, building prototypes, testing programmes, implementing and maintaining programmes. The research subject is legislative candidates and the object is the Gerinda party which conducts the selection of legislative candidates. Application design assisted by Unified Modelling Language (UML) modelling techniques can provide the best system design, then the calculation results will be ranked to get the optimal alternative. Then the data analysis technique uses the Simple Additive Weighting (SAW) method. This research produces the name of the candidate who will be elected by building a system with the application of the SAW method. Of the 9 people who registered as prospective candidates.